2020
DOI: 10.1177/2057158520966949
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ experiences of peer learning in a dedicated educational unit in municipal home healthcare: A phenomenological study

Abstract: The shift from hospital-based nursing care to municipal home healthcare has led to the provision of more diverse, complex and advanced nursing care in this context. This poses challenges for undergraduate nursing students’ clinical education. The aim of this study was to describe nursing students’ experiences of learning nursing care through peer learning in a dedicated educational unit in municipal home healthcare. Data were collected through interviews with seven nursing students. The analysis was based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Students are actively engaged in the cognitive process during these talks because they must explain their replies to their classmates with supporting rationales. With the consistency of the study finding the previous research that stated that peer teaching fosters student's deep understanding and knowledge, such as the study of [31], which showed a significant improvement in selecting the correct answer of student's knowledge after peer teaching, and the previous studies of [32][33][34], which show that the plurality of nursing students who were taught by colleagues education received excellent knowledge scores. The finding of existing study showed that slightly more than half of nursing students who were taught the selected clinical skills through peer teaching have an excellent plus grade of practice, whereas half of nursing students who were taught the other clinical skills through traditional lecture have a very good grade.…”
Section: Discussionsupporting
confidence: 78%
“…Students are actively engaged in the cognitive process during these talks because they must explain their replies to their classmates with supporting rationales. With the consistency of the study finding the previous research that stated that peer teaching fosters student's deep understanding and knowledge, such as the study of [31], which showed a significant improvement in selecting the correct answer of student's knowledge after peer teaching, and the previous studies of [32][33][34], which show that the plurality of nursing students who were taught by colleagues education received excellent knowledge scores. The finding of existing study showed that slightly more than half of nursing students who were taught the selected clinical skills through peer teaching have an excellent plus grade of practice, whereas half of nursing students who were taught the other clinical skills through traditional lecture have a very good grade.…”
Section: Discussionsupporting
confidence: 78%